Gulf breeze - Hill, Gerri (Tallahassee, FL : Bella Books, 2004)
A wildlife biologist returns to the Texas Gulf Coast to manage a habitat project, where she meets a woman wildlife photographer with whom she falls in love.
Keywords: Women biologists -- Fiction; Women photographers -- Fiction; Lesbians -- Fiction; Gulf Coast (Tex.) -- Fiction; Love stories